If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(y+3)=8y+32
We move all terms to the left:
4(y+3)-(8y+32)=0
We multiply parentheses
4y-(8y+32)+12=0
We get rid of parentheses
4y-8y-32+12=0
We add all the numbers together, and all the variables
-4y-20=0
We move all terms containing y to the left, all other terms to the right
-4y=20
y=20/-4
y=-5
| 1/2x-4=1/4x+1 | | -9-15+16m=12+10 | | 6x+15-10=47 | | 12+9m=66 | | 6/7k=30 | | 12a-4=-5 | | 3x+4x-5=3x+3 | | 8x-13=25-6 | | –4−4t=–3t | | 9x+7=2x+6 | | -5w-40=-9(w+8) | | 3(4b-2)=2(5b-6)+3b | | 5x+3=2x+55 | | 16+10v=8v | | 2x-15x-5+42=180 | | x+100+130+66=360 | | -19-3z=-22 | | 5/3b-11=8/b+4 | | -x-163=12x+48 | | -12+6k=6(2+3k) | | 2/3x5/9= | | -5x+-10=35 | | 14t+13=5 | | 3x=20+2x | | 11-3=t | | 3z-19=-20 | | 6(y-5)=-4y+20 | | 5-2f=-7f | | -2-x7+3x=10 | | -20+y/3=8 | | 3x+x+2=5x-2 | | (1/2)(x)+3=-22x |